The Hite Report on Love, Passion and Emotional Violence - Hite Shere; Optima (1991)
This book provides a new cultural interpretation of love and female psychology. Acknowledgements, The Emotional Contract: Emotional Life in Marriages and Love Relationships with Men, The Major Problems in Love Relationships, Fighting and Arguing in Relationships: What Do They Mean?, The Ideology Behind the System - Women's Giving and Men's ''Being'', Being Single: Women and Autonomy, Four Single Women Describe Their Lives, Dating Men: Fun or Russian Roulette?, Inside Dating Relationships: How Are Women Feeling?, Loving Men Who Are ''Bad For You'': The Myth of Female Masochism, Single Women Debate Whether to Marry, Marriage and the Nature of Love, Extramarital Sex and Affairs, Finances and Housework, Women's Feelings about Divorce, Women Loving Women, To Transform the Culture with Our Values, Loving Men at This Time in History, Friendships Between Women: Another Culture and Another Way of Life, To Make a World in Which More Love Can Flourish, Bibliography and Additional Reading.